Comparing the Potential of Marker-Assisted Selection and Genomic Prediction for Improving Rust Resistance in Hybrid Wheat - Beukert, Ulrike; Thorwarth, Patrick; Zhao, Yusheng; Longin, C. Friedrich H.; Serfling, Albrecht; Ordon, Frank; Reif, Jochen C. (Frontiers in Plant Science, 2020)
Improving leaf rust and stripe rust resistance is a central goal in wheat breeding. The objectives of this study were to (1) elucidate the genetic basis of leaf rust and stripe rust resistance in a hybrid wheat population, (2) compare the findings using a previously published hybrid wheat data set, and (3) contrast the prediction accuracy with those of genome-wide prediction. The hybrid wheat population included 1,744 single crosses from 236 parental lines. The genotypes were fingerprinted using a 15 k SNP array and evaluated for leaf rust and stripe rust resistance in multi-location field trials. We observed a high congruency of putative quantitative trait nucleotides (QTN) for leaf rust susceptibility between both populations. This was not the case for stripe rust susceptibility. Accordingly, prediction accuracy of the detected QTN was moderate for leaf rust but low for stripe rust susceptibility. Genome-wide selection increased the prediction accuracy slightly for stripe rust albeit at a low level but not for leaf rust. Thus, marker-assisted selection seems to be a robust and efficient tool to improve leaf rust resistance in European wheat.